Turn-taking in cinematic discourse: linguistic characteristics and practical implications for ESP teaching - Lavrinenko, Iryna; Shevchenko, Iryna (My University, 2019)
The article focuses on the issues of teaching turn-taking for ESP students in blended distance learning courses at B2 level. It lays the rationale for the use of film episodes of business interaction in distance learning highlighting turn-taking as an operational meta- discursive category. In multimodal cinematic discourse, turn-taking is performed by heterogeneous semiotic resources: linguistic, non-linguistic, cinematic codes and underpinned by intersubjectivity. Turn-taking strategies of initiating and responding types are viewed as a system of interactional dialogic communication management which includes discursive means of turn-claiming, attempt- suppressing and turn-yielding where each type is actualised by its own set of tactics and techniques. We claim that ESP learners need to know the main parameters for turn-taking in oral professional communication; such as the participants’ stance, speaker – hearer relations and their intersubjectivity, the transition point in a conversation, discourse situations, and specific semiotic resources. In cooperative discourse situations, turn-claiming and turn-yielding strategies are determined by initiating tactics of statement or interrogation. Unlike this, in conflict situations, turn-taking strategies depend upon initiating tactics of statement, interrogation, order, inducement and predetermine responding tactics. In asynchronous and blended formats of distance learning, the preferable delivery methods for this material include video recordings and digital games which facilitate receiving new information and motivate students to practice new communicative skills.
Keywords: ESP; distance learning; communicative competence; turn-taking; strategy; intersubjectivity; cinematic discourse; conflict situation; cooperative situation